LUTO PROLONGADO DE FAMILIARES E SUA INTERFACE COM OS CUIDADOS PALIATIVOS ONCOLÓGICOS. - PEREIRA, Clarissa Pires (2021)
Introduction: There are a considerable number of bereaved family members who may be subject to prolonged grief and depression. Palliative care has extreme relevance for the prevention of complicated grief, respecting and considering the fundamental role of the family in the process of illness and grief. Prior intervention and the existence of guidelines and services aimed at supporting the grief of the family member are necessary. Objectives: To evaluate the grieving process in relatives of patients followed in an oncological palliative care unit and investigate the prevalence of prolonged mourning and factors associated with the occurrence of this, the interface with palliative care care and the interlocution between prolonged grief and depression. Method: The study was analytical, observational, cross-sectional and with quantitative approach to the data. Eighty family members/caregivers participated in a referral hospital in oncology. They were applied: socio-demographic questionnaire, postmortem follow-up questionnaire, PG 13 prolonged grief assessment instrument and Beck depression inventory (BDI). For statistical analysis, the Chi-Square and the logistic regression model with heirarchical approach were used. Results and discussion: Of the 80 participants, It was observed that 25% presented criteria for prolonged mourning and of these, 69.2% exhibited moderate to severe depressive symptoms. Most of the companions with prolonged mourning were female (27%), 27.5% were children of the patients, 30.8% aged between 33 and 45 years, 32% single, 89.9% who still could not resume their daily activities and 88.9% who considered the support of the palliative care team as poor. The family members who characterized the support of the palliative care team as good, only 33.4% presented criteria for prolonged mourning. As factors associated with the occurrence of prolonged grief, losing a female loved one, there is a 16.47 times more chance of the family member developing prolonged grief; the bereaved who practices physical activity is 7% less likely to have prolonged grief; receiving significant support from the palliative care team causes 13% less chance of prolonged mourning in the companion. and those with prolonged grief are 78.77% more likely to report depression. Conclusions: Prolonged mourning and depressive symptoms of moderate to severe levels may occur in family members followed up in an oncological palliative care unit. As factors associated with the occurrence of prolonged mourning, the loss of a female loved one was verified, the bereaved subject did not perform physical activity as a form of self-care, the support provided by the palliative care team to the family member's grieving process, and the association with depressive symptoms. Prolonged grief disorder preceded moderate to severe depressive symptoms.